Cutting costs more than trees - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A combination of sawdust and wheat bran moulded together into a banana-shaped briquette is now an alternative to wood and charcoal fuel. The Jerriton Bakery and Coffee Factory in Kampala, which developed the briquette, cut down its fuel costs for...